EuAuGe Type Indides RAgIn (R = Ca, Sr, La, Eu). Issue 14 (22nd June 2017) - Stein, Sebastian; Schmolke, Kai Heinz; Block, Theresa; Heletta, Lukas; Hoffmann, Rolf‐Dieter; Pöttgen, Rainer
Abstract : The equiatomic intermetallic phases CaAgIn [ a = 482.75(7), b = 750.0(1), c = 835.5(1) pm], SrAgIn [ a = 495.86(5), b = 794.71(9), c = 851.89(9) pm], LaAgIn [ a = 489.99(5), b = 767.93(9), c = 837.53(9) pm], and EuAgIn [ a = 493.02(7), b = 781.6(1), c = 844.2(1) pm] were synthesized from the elements in sealed niobum containers. They crystallize with the EuAuGe type structure, space group Imm 2. The four structures were refined from single‐crystal X‐ray data. The silver and indium atoms build up orthorhombically distorted, puckered Ag3 In3 hexagons, which are stacked in AA′ sequence, leading to direct Ag–Ag and In–In interlayer bonding (e.g. 303 and 304 pm in CaAgIn). Temperature dependent magnetic susceptibility measurements show a magnetic moment of 7.40(1) μ B per europium atom. EuAgIn orders antiferromagnetically at 5.7(5) K. The divalent nature of europium is also evident from 151 Eu Mössbauer spectra: δ = –10.50(1) mm· s –1 at 78 K. Abstract :